Control of A-system amino acid transport by a second regulatory gene R2 in Chinese hamster ovary cells CHO-K1 and the possible connection of this gene with insulin activity. - Moffett, J (1987)
Evidence based on a study of alanine-resistant (Alar), constitutive mutants of CHO-K1 cells and the conditions that favor stimulation of the A system of amino acid activity supports the model that the A system of amino acid transport in these cells is repressible and under negative control of regulatory gene R1. In this study, we show that mutant Alar6, when grown under conditions of repression, has an A system of amino acid transport activity similar to that of the derepressed parental cell line, CHO-K1 (wild type) and of the fully constitutive mutant in gene R1, Alar4. However, the A system of Alar6 is further derepressible. The Vmax for proline transport through this system in mutant Alar6 is four times that of the parental culture, with no significant change in Km. Analysis of hybrids produced by crossing mutant Alar6 with the parental culture and with Alar4 shows that mutant Alar6 is recessive to wild type and complements mutant Alar4. Although the amino acid transport A system of CHO-K1 is stimulated by insulin, mutant alar6 is not stimulated by insulin. These results support the hypothesis that mutant alar6 results from mutation in another regulatory gene, R2, that, in conjunction with gene R1, negatively controls the expression of a structural gene for the A-system transport. Evidence also indicates that R2 gene product is not responsive to amino acids and that insulin stimulation of the A system may result from insulin inactivation of this repressor.